Peningkatan Keterampilan Menyimak Melalui Model Pembelajaran Think-Pair-Share Siswa SMA Negeri 1 Pangkep: Improving Listening Skills Through Think-Pair-Share Learning Model for Students of SMA Negeri 1 Pangkep - Rahmadhani, Nurul; Muin, Nurmiah; Puspitasari, Andi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to improve students' listening skills through the Think-Pair-Share (TPS) learning model on short story learning materials for class XI Baik SMAN 1 Pangkep. Students' short story listening skills are still very low because students are less interested in learning and do not understand the intrinsic and extrinsic elements in more depth in short stories. The use of models and media that are less interesting makes students bored. This type of research is Classroom Action Research (CAR) which aims to improve the quality or problem solving in the subjects studied and observe the level of success or consequences of their actions, to then receive additional actions which are improvements to the action. In the pre-cycle, the average student score was 45 and 4 students or 11% achieved the KKM. In cycle 1, the average student score was 64 and 10 students or 28% achieved the KKM. The average student score in cycle 2 increased by 81 and 33 students or 92% achieved the KKM. Based on the results of the research and discussion above, it can be concluded that the use of the Think-Pair-Share model can improve the listening skills of grade XI Baik students of SMAN 1 Pangkep. Research data conducted during the pre-cycle stage to cycle 2 showed different results. Each cycle showed an increase in student learning outcomes.